2018
DOI: 10.1038/s41467-018-04095-x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenate anions as organocatalysts for benzylic chloromethyl coupling polymerization via C=C bond formation

Abstract: Organocatalytic polymerization reactions have a number of advantages over their metal-catalyzed counterparts, including environmental friendliness, ease of catalyst synthesis and storage, and alternative reaction pathways. Here we introduce an organocatalytic polymerization method called benzylic chloromethyl-coupling polymerization (BCCP). BCCP is catalyzed by organocatalysts not previously employed in polymerization processes (sulfenate anions), which are generated from bench-stable sulfoxide precatalysts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Finally, the above‐described procedure has successfully been applied to the coupling polymerization of compounds bearing two chloromethyl substituents on the same or on different linked aromatic rings, as depicted in Scheme . Such a benzylic chloromethyl coupling polymerization links the monomers by C=C bond formation, always employing CPME (or MTBE) as the preferred solvent …”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Finally, the above‐described procedure has successfully been applied to the coupling polymerization of compounds bearing two chloromethyl substituents on the same or on different linked aromatic rings, as depicted in Scheme . Such a benzylic chloromethyl coupling polymerization links the monomers by C=C bond formation, always employing CPME (or MTBE) as the preferred solvent …”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Previous work [26] from our laboratories demonstrated that sulfenate anions (ArSO À ) can catalyze polymerization of bis-benzylic chlorides yielding PPVs with high yields and low dispersity (Đ ), but required heating at 80°C. We expected selenenate anions could provide PPV derivatives under milder conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We recently introduced the first sulfenate anion catalysts for the dehydrohalogen coupling of benzyl chlorides to make stilbenes [2] and the cross-coupling of benzyl chlorides with benzaldehydes under basic conditions to give diaryl acetylenes. [4] Recently, there has been significant interest and substantial progress in development of organocatalysts based on the heavier chalcogenide, selenium. This class of catalysts enabled the introduction of benzylic chloromethyl coupling polymerizations (BCCP), which is useful for the synthesis of poly(stilbenes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases can also be found, for example, in the synthesis of poly(phenylene vinylene)s or their nitrogen-incorporating analogues, where the coupling process directly furnishes double bonds. 135,136 The synthesis of GNRs is more complex, both conceptually and experimentally, since the growth of the polymer requires the formation of multiple bonds in sequential processes. Referring, again, to NG synthesis as a test case, one would have to first synthesize polyarylenes (e.g., with naphthalene or anthracene units) or polyphenylenes with additional oligophenylene side arms as precursor polymers.…”
Section: Solution Synthesismentioning
confidence: 99%